PERAN PENDIDIKAN PANCASILA DALAM MEMBENTUK CIVIC RESPONSIBILITY & KESADARAN MULTIKULTURAL SISWA KELAS X SMA NEGERI COLOMADU TAHUN 2025 - Naesya, Kanaya; Sutoyo; Supeni, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the role of Pancasila Education in shaping civic responsibility and multicultural awareness of students, especially in grade X. This study is motivated by the importance of strengthening civic character and tolerance amidst the diversity of Indonesian society. This research uses a qualitative approach with a descriptive qualitative research type. Data were obtained from primary and secondary sources through observation, interview, and documentation techniques. Data validity was tested through source triangulation and technical triangulation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that Pancasila Education plays a significant role in shaping students' attitudes of responsibility as demonstrated through understanding of rights and obligations, discipline, compliance with rules and participation in school activities. Pancasila Education also contributes to fostering students' multicultural awareness, this is reflected in students' attitudes that respect differences and are able to work together in diverse environments. Pancasila Education teachers not only have a role as teachers but also play a strategic role as motivators, facilitators, and role models for students.